Miskonsepsi Siswa dalam Menyederhanakan Ekspresi Aljabar berdasarkan Kerangka Asimilasi dan Akomodasi - Rahma, Lilavati Vijaganita; Alifiani (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2024)
This study adopts a qualitative approach with a descriptive research design. The subjects of this study consist of six students from class X of a high school during the second semester of the 2023/2024 school year. The data analysis process includes three stages: data reduction, data presentation, and drawing conclusions. The validity of the findings was ensured through triangulation, which involved comparing data from students' work, interview results, and observation results. The findings revealed that students exhibited seven types of misconceptions leading to errors in simplifying algebraic expressions: (1) conjunction error, (2) exponent error, (3) reversal error, (4) difficulties with variables, (5) substitution error, (6) equation formation errors, and (7) a commutative-like terms error. These misconceptions were attributed to inappropriate assimilation and a lack of accommodation.